Exploring the Relationships Between Yield and Yield-Related Traits for Rice Varieties Released in China From 1978 to 2017 - Li, Ronghua; Li, Meijuan; Ashraf, Umair; Liu, Shiwei; Zhang, Jiaen (Frontiers in Plant Science, 2019)
Despite the evidences from previous case studies that agronomic traits contribute to the yield of different rice (Oryza sativa L.) varieties, it remains unclear whether it is true at ecotype level. Keeping in view the relations between yield and other agronomic traits, the present study was accomplished by using an extensive dataset of traits of 7686 rice varieties released in China from 1978 to 2017. We assessed the associations between yield and other agronomic traits for four different rice ecotypes i.e., indica inbred, indica hybrid, japonica inbred and japonica hybrid. We found that associations between agronomic traits and yield were ecotype dependent. For both indica inbred and hybrid rice varieties, increased filled grain number per panicle, 1000-grain-weight, plant height, panicle length, grains per panicle, seed setting rate, long growth period, and low panicle number per unit area, low seed length/width ratio have accounted for high grain yield. In japonica inbred and hybrid rice varieties, we found that only high panicle number per unit area and long growth period led to high grain yield. As for the indirect factors, a positive effect of growth period on yield was consistently observed in each ecotype; the positive effects of plant height on yield were found for indica inbred, indica hybrid and japonica, while negative for japonica. Taken together, our findings have potentially valuable implications for improving the breeding of varied rice ecotypes.